Meningkatkan Kompetensi Guru Sasaran dalam Proses Pembelajaran Melalui Supervisi Akademik di SMPN 21 Mataram - Zainudin Zainudin (Universitas Pendidikan Mandalika (UNDIKMA), 2016)
This research was conducted in two cycles, activities in every cycle had four stages namely planning, acting, observing, and reflecting. Indictaor of completeness in this research was 1) result of headmasters’ observation or teachers’ observation as long as guiding process has gotten mean score > 4,0, 2) reselt of teachers’ mean score in learning process was > 85% with mean score > 80,00 (good category). Result of research in cycle I mean score of headmasters’ observation (3,80), mean score of teachers’ observation (3,20) and result of target academic supervisor was (78,17). In cycle II mean score of headmasters’ observation (4,40) with percentage of completeness (100%, mean score of teachers’ observation (4,30) with percentage of completeness (100%) and mean score of target academic supervisor (85,49) with percentage of completeness (100%). Indicator of completeness had been reached, research was stated success and stopped in cycle II. Conclusion; result of research in cycle II showed improved for target teacher competence in learning process at real classroom. It suggested for other headmasters conducted similar research in effort to improve teachers’ competence, and for teachers in order to conduct learning process based on scenario which has been planned well, responsible, really in improving students learning achievement suitable with their subject.